RANCANG BANGUN APLIKASI ADMINISTRASI PENGELOLAAN PENELITIAN DAN PENGABDIAN MASYARAKAT (STUDI KASUS INSTITUT BISNIS DAN INFORMATIKA STIKOM SURABAYA) - Sari, Nita Maya; Wurijanto, Tutut; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Institute for Business and Information Technology, hereinafter referred Stikom Surabaya is one of the private universities. To support the Tri Dharma College Stikom Surabaya has a Research and Community Service (PPM). Constraints existing at the time of submission of the proposal that still use hardcopy, so it takes at the time of assessment because the operator must distribute the proposal which led to the reviewer can not immediately make an assessment. Announcement of the results of the assessment and the schedule operator exposure is done through email one by one from the registration file for support, so the announcement process takes time. Making the report was done by looking at the file registration and assessment unprocessed. Those problems can be solved by the creation of applications that can simplify the submission of proposals to the final report, as well as help improve service to the proposer, reviewer and leadership in conducting administrative activities PPM management. After testing it can be concluded that the applications made to assist and accelerate the process of administrative activities PPM. In addition computerized registration is done so as to reduce the use of paper (paperless) and pelayanaan registration and assessment can be accessed anywhere and anytime. This application provides information about the activity of the faculty in conducting research and community service.